Use of specific polysaccharide‐immobilized monodisperse poly(glycidyl methacrylate) core–silica shell microspheres for affinity purification of lectins. (22nd October 2014) - Antonyuk, Volodymyr; Grama, Silvia; Plichta, Zdeněk; Magorivska, Iryna; Horak, Daniel; Stoika, Rostyslav
Abstract Immobilization of polysaccharides (yeast mannan and gum arabic) on the macroporous poly(glycidyl methacrylate) monodisperse microspheres coated with silica (SiO2)‐containing amino groups on the surface was used to prepare affinity sorbents for lectin purification. The efficiency of isolating mannose specific Pisum sativum lectin was demonstrated on sorbent with immobilized yeast mannan and that of galactose specific Glycine hispida lectin on sorbent with immobilized gum arabic. The microspheres with immobilized polysaccharides can be used for selecting an affinity sorbent for purification of other mannose‐ and galactose‐specific lectins. In contrast to yeast mannan, the gum arabic immobilized on the microspheres possesses much narrower specificity and is suitable for purification of only those galactose specific lectins which interact well with l‐rhamnose or l‐arabinose. The synthesized macroporous particles are capable of immobilizing 50 mg of polysaccharide per 1 g of the matrix, which is 10 times higher than the capacity of epoxy‐activated Sepharose 6B. That makes it possible to obtain the same lectin quantity using a column of 10 times smaller volume. Another advantage of novel affinity sorbents comparing corresponding Sepharose gels is the possibility of sorbent drying after use. Copyright © 2014 John Wiley & Sons, Ltd.